Simbiosis Mutualisme: Hukum Islam dan Perbankan Syariah - Arifin, Asriadi; Abubakar, Achmad; Haddade, Hasyim; Ramadhani, Syamsinar (Program Studi Ekonomi Syariah IAIN Parepare, 2023)
Studies that formulate sharia banking and Islamic law in force in Indonesia have never been studied before, so researchers are currently giving the term symbiosis of mutualism because between sharia banking and Islamic law provide mutual benefits. This library research is a research whose data comes from library sources, namely literature review through library research. The main reference sources in research are adapted from various experts who talk about banking, including: Thamrin Abdullah & Francis Tantri in his book